Pengaruh Podcast (Siniar) Youtube terhadap Peningkatan Keterampilan Berbicara - Ummul Qura; Nini Ibrahim; Prima Gusti Yanti; Irwan Baadilla (Ranah: Jurnal Kajian Bahasa, 2022)
Currently, podcasts (Siniar) are programs that are very popular with the public, not students. Inside the program, there is a speaking activity which is a fundamental aspect for students. The problem that occurs in learning speaking skills is that conventional methods are still often used. Through the broadcast, it is hoped that learning activities will be more innovative and able to improve students' speaking skills. Thus, the purpose of the study was to see the effect of YouTube podcasts on students' speaking skills. The quantitative method applied in this research is quasi-experimental. The population used were all fourth-semester students of the Pendidikan Bahasa dan Sastra Indonesia (PBSI) FKIP UHAMKA. Determination of the sample with a non-probability sampling technique. The independent variable in this study is speaking skills, while the variable is the YouTube Podcast program. Data were collected through dissemination instruments in the form of questionnaires on Podcasts and speaking practice activities. The results showed that there was a constant regression coefficient score with a value of 0.296. This score means that if each student adds podcast activity, then speaking skills increase by 0.296. In other words, for every 1% increase in the value of the variable during podcast shows, the value of speaking skills increases by 0.296. Therefore, this study concludes that there is an effect between watching YouTube Podcasts on students' speaking skills.